1975
DOI: 10.1107/s0567739475001295
|View full text |Cite
|
Sign up to set email alerts
|

Analytic approximation to incoherently scattered X-ray intensities

Abstract: The theoretically calculated incoherently scattered X-ray intensities of Cromer & Mann [J. Chem. Phys. (1967). 47, 1892-1893 and Cromer [J. Chem. Phys. (1969). 50, 4857-4859] for the elements 2 to 95 and 102 have been fitted to an analytic function. The coefficients of fit are tabulated and the accuracy of the fitting is discussed. The accuracy is very good for sin 0/2 <_ 1.5 ~-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 5 publications
2
42
0
Order By: Relevance
“…The Compton scattering contribution was calculated using the fitting parameters provided in ref. [7] for the different elements. The normalization factor was obtained by the Krogh-Moe-Norman method.…”
Section: Introductionmentioning
confidence: 99%
“…The Compton scattering contribution was calculated using the fitting parameters provided in ref. [7] for the different elements. The normalization factor was obtained by the Krogh-Moe-Norman method.…”
Section: Introductionmentioning
confidence: 99%
“…For all the compositions studied, positions of maxima and minima of the structure factors of -irradiated and annealed glasses coincide with those of radiation-modified Ge 25 Sb 15 S 60 and Ge 35 Sb 5 S 60 glasses. Main difference between -irradiated and annealed glasses is observed only in the intensity of the FSDP for As-enriched composition Ge 16 As 24 S 60 for which the prepeak becomes weaker and broader under irradiation (Fig. 1b) similarly to the binary As 2 S 3 glass [19].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, for all the glasses studied, it is found that radiation impact results in weakening and broadening of the FSDP with the first peak at r = 2.26-2.27 Å and the second peak at r = 3.55-3.60 Å; the effect is the largest one for Ge 16 As 24 S 60 (x = 16), smaller for Ge 24 As 16 S 60 (x = 24), and practically invisible for Ge 32 As 8 S 60 (x = 32) and Ge 36 As 4 S 60 (x = 36) alloys. …”
Section: Fig 2 (A) the Pair Distribution Functions G(r)mentioning
confidence: 95%
See 2 more Smart Citations